Morphological properties of underwater soils of river deltas - A. N. Tkachenko; M. N. Kozachuk; O. V. Tkachenko (Бюллетень Почвенного института им. В.В. Докучаева)
The results of the study of the morphological properties of underwater soils in the deltas of the Volga, Don and Kuban rivers are shown. This paper is based on field descriptions of profiles of underwater soils found in deltas. Genetic horizons have been identified, their basic properties (pH, Eh, electrical conductivity, grain size composition, organic carbon content) have been studied and the main types of soils, which are formed under different types of sedimentation and under different types of aquatic vegetation, have been described. Names of horizons and types of soils are given due to the classification of underwater soils (aquazems) of the Volga delta, that had been proposed previously. The diversity of underwater soils of three deltas has been studied, and the properties of the same soil types formed in different deltas have been compared. The features of underwater soils formation are described; the difference between the factors of underwater and terrestrial soil formation is discussed. It is shown that the number of occurring soil types depends on the diversity of the emerging types of aquatic landscapes and the contrast of the conditions of migration and accumulation of matter. Necessary conditions for the forming of underwater soils and the possibility of relating bottom sediments to soil formations are discussed. Our results are indicative of the need of studying bottom sediments with soil-like profile from the standpoint of soil science and the inclusion of aquazems into the modern Russian soil classification.